Optimization of a method for identifying the flow regime and measuring void fraction in a broad beam gamma-ray attenuation technique. (18th May 2016) - Nazemi, E.; Roshani, G.H.; Feghhi, S.A.H.; Setayeshi, S.; Eftekhari Zadeh, E.; Fatehi, A.
Abstract: A gamma-ray transmission technique is present to measure the void fraction and identify the flow regime of a two-phase flow using two detectors which were optimized in terms of detector orientation. Using Monte-Carlo simulation, experimental results were utilized for training an artificial neural network. Radial Basis Function was used to classify flow regimes (annular, stratified and bubbly) and predict the value of void fraction. All of the training and testing data sets were determined correctly and the mean relative error percentage of predicted void fraction was less than 1.5%. Although the method was applied to a certain pipe size in a static flow configuration, it provides a framework for application to other configurations. Highlights: High precision measurement structure with only using two detectors was proposed. Optimal positions for the two detectors were obtained using Monte-Carlo simulation. An experimental structure was set up and the required data was obtained. RBF was used in order to classify data and predict the void fraction. All of the training and testing data sets were determined correctly.